2020
DOI: 10.5194/hess-24-3475-2020
|View full text |Cite
|
Sign up to set email alerts
|

Importance of snowmelt contribution to seasonal runoff and summer low flows in Czechia

Abstract: Abstract. The streamflow seasonality in mountain catchments is often influenced by snow. However, a shift from snowfall to rain is expected in the future. Consequently, a decrease in snow storage and earlier snowmelt is predicted, which will cause changes not only in seasonal runoff distribution in snow-dominated catchments, but it may also affect the total annual runoff. The objectives of this study were to quantify (1) how inter-annual variations in snow storages affect spring and summer runoff, incl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 52 publications
1
24
2
2
Order By: Relevance
“…As the dS2 model does not include dams and other reservoirs, this signal can be attributed to a change in discharge production. Secondly, a recent study investigating the response of several basins in Czechia to changes in snowmelt concluded that snowmelt started earlier in the year, which also reduced summer low flows via baseflow (Jenicek and Ledvinka, 2020). However, our study shows that low flows during September and October actually increased when only snow processes are considered.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…As the dS2 model does not include dams and other reservoirs, this signal can be attributed to a change in discharge production. Secondly, a recent study investigating the response of several basins in Czechia to changes in snowmelt concluded that snowmelt started earlier in the year, which also reduced summer low flows via baseflow (Jenicek and Ledvinka, 2020). However, our study shows that low flows during September and October actually increased when only snow processes are considered.…”
Section: Discussioncontrasting
confidence: 62%
“…The evaporation correction factor is included to correct any bias errors in the forcing data. According to Boussinesq's theory of sloping aquifers (Rupp and Selker, 2006) and the results found in Karlsen et al (2019), systems with higher slopes are expected to show higher discharge sensitivity values. Therefore, the discharge sensitivity parameters were defined as a linear function of the slope of each pixel, based on the hypothesis that regions with steeper slopes show a more responsive storage-discharge relation than regions with gentle slopes.…”
Section: Ds2mentioning
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, the assumption that incoming solar radiation is well represented by air temperature does not al-ways hold, such as in high-elevation catchments where temperature seldom rises above the freezing point (Gabbi et al, 2014;Pellicciotti et al, 2005) or in conditions in which sublimation from the snowpack becomes a significant process (Herrero and Polo, 2016). Such issues led to the development of extended formulations including additional variables such as wind speed or relative humidity to improve the snowmelt estimation (Zuzel and Cox, 1975) or even hybrid methods combining energy-based and temperature-based approaches, such as the inclusion of a radiation component in temperature-based models (Hock, 1999;Kane et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Also, thanks to the combination of these factors, the summer droughts at CHA have not been as pronounced as in the KLI or ROT catchments so far. However, according to recent studies, the proneness of montane, mid-latitude catchments to summer water scarcity is expected to increase in the next decades in concordance with the ongoing warming (Bales et al, 2018;Brunner & Tallaksen, 2019;Hotovy & Jenicek, 2020;Jenicek & Ledvinka, 2020 Langhammer, & Beudert, 2015). This fact can be related with the usage of shorter data series, which did not cover the last decade.…”
Section: Discussionmentioning
confidence: 99%